Exploring feminist consciousness through music in Eileen Chang’s postcolonial narratives - Ruikai Yuana; Ravichandran Vengadasamy; Melissa Shamini Perry; Ruzy Suliza Hashim (Penerbit Universiti Kebangsaan Malaysia, 2024)
The characters, stories, and various issues related to female consciousness discussed in literary texts can serve as a conduit for readers to understand the complex of gender, culture, and identity in postcolonial contexts. This article explores how Chinese-American author Eileen Chang portrays the realization of female consciousness in women from post-colonial Hong Kong and Shanghai through music. Drawing upon the theories of Lucy Green and Marcia J. Citron, this study conducts a critical content analysis of two of Chang’s works Aloeswood Incense (1944) and Love in a Fallen City (1943). It examines specific dialogues and discourses related to themes of music, gender, and cultural identity. In this context, the main character Weilong in one story transforms her engagement with music and education, showcasing her journey towards self-realization and empowerment, while the protagonist Liusu in the other narrative is depicted as navigating through societal expectations and personal aspirations, with music playing a significant role in her self empowerment. The research findings suggest Chang’s works reflect the expectations and limitations of society towards women, while also revealing the crucial role of music in shaping and expressing female identity. This article can serve as a means for readers to learn about how women’s roles and identities in relation to music were shaped and how cultural background can help create similar outcomes.